Experiences of HIV pre-exposure prophylaxis users during the flood in Porto Alegre - Deise Taurino Ramos; Camila Rocha Silveira; Amiry Monteiro Sanca; Tiago Sousa Paiva; Rosana Maffacciolli; Deise Lisboa Riquinho (Revista Gaúcha de Enfermagem)
ABSTRACT Objective: To understand the experiences of users of human immunodeficiency virus pre-exposure prophylaxis during the flood in Porto Alegre, Rio Grande do Sul, Brazil. Method: This is a qualitative study. Twenty-five users participated, and data collection was conducted through semi-structured interviews held via telephone, from May to July 2024. Thematic content analysis was adopted. Results: The findings were organized into two empirical categories: “Collective tragedy: repercussions for everyday life,” which revealed feelings of loss, fear, and emotional instability in the face of the disaster; and “The PrEP is over: strategies and (dis)continuity,” with one subcategory, “Relationship with the (Non)Service”. Disruptions in access to medication, failures in institutional communication, and a sense of insecurity regarding continuity of care were evident. Conclusion: PrEP use continuity was compromised during the disaster, highlighting the need for public policies that ensure continuous care in adverse contexts, through emergency protocols and clear, accessible communication.